Contribution of Emotional Intelligence, Coping, and Social Support towards Adjustment and Academic Achievement amongst Fresh Students in the University - Abdullah, Maria Chong (2008)
Adjustment is a significant predictor of academic achievement amongst fresh students in university. Adjustment problems can affect the students’ performance if they are not overcome. Thus, this study aims to investigate the role of students’ overall adjustment as a mediator in predicting the relationship between emotional intelligence, coping, and social support with academic achievement in the university. Besides that, this study also explores students’ level of academic achievement, adjustment, emotional intelligence, coping effort, and their level of satisfaction towards the availability of social support at the university. Using correlational descriptive design, this study involved 250 first semester students at a local public university. Instruments employed to measure the research variables in this study are: Student Adaptation to College Questionnaire (to assess adjustment to university), Mayer-Salovey-Caruso Emotional Intelligence TestTM (to assess emotional intelligence), Ways of Coping Questionnaire (to assess coping effort), and Interpersonal Social Evaluation List-College Version (to assess social support). Data was analyzed using descriptive and inferential statistics. Research findings showed that majority of the students have a moderate overall adjustment level, as well as for the academic adjustment, social adjustment, personal-emotional adjustment, and goal commitment/institutional attachment dimensions. Students also demonstrated a low level of emotional intelligence, which was at the developmental level. Research findings show that students’ level of coping effort and their statisfaction towards social support that was available at the university were moderate. Academic adjustment dimension was found to be the highest predictor for academic achievement followed by the personal-emotional adjustment dimension. Findings of the study indicated that there were significant differences in students’ overall adjustment level based on their gender and academic achievement. Male students’ overall level of adjustment was found to be higher compared to female students. Students who achieved higher grade point average were found to have higher overall level of adjustment compare to those who achieved low grade point average. The path analysis results showed that the overall adjustment was an important mediator in explaining the relationship between emotional intelligence, coping, and social support and students’ academic achievement. It was found that social support perceived the highest mediating effect from overall adjustment in predicting students’ academic achievement. Research findings also indicated that emotional intelligence contributed the highest overall effect on students’ academic achievement. In conclusion, this study shows that students’ psychological attributes such as emotional intelligence, coping, and social support have a positive impact on academic achievement through their overall adjustment as mediator.